2013
DOI: 10.1002/mas.21389
|View full text |Cite
|
Sign up to set email alerts
|

Protein modifications by electrophilic lipoxidation products: Adduct formation, chemical strategies and tandem mass spectrometry for their detection and identification

Abstract: The post-translational modification of proteins by electrophilic oxylipids is emerging as an important mechanism that contributes to the complexity of proteomes. Enzymatic and nonenzymatic oxidation of biological lipids results in the formation of chemically diverse electrophilic carbonyl compounds, such as 2-alkenals and 4-hydroxy alkenals, epoxides and eicosanoids with reactive cyclopentenone structures. These lipoxidation products are capable of modifying proteins. Originally considered solely as markers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 108 publications
(163 reference statements)
2
38
0
2
Order By: Relevance
“…Presence of the second carbonyl function (assuming it is in α position) results in a higher electrophilicity of the first carbonyl group. Indeed, glyoxal, shown here as the most reactive oxoLPP (15 modification sites), was recently classified as aldehyde with the highest calculated electrophilicity and softness [97], followed by HNE, MDA and HHE [98], which closely resembled the reactivity detected in our study (nine, ten and five modification sites for HNE, methylglyoxal/MDA and HHE respectively). One more reason for the high reactivity of short chain dicarbonyls could be the relatively high hydrophilicity.…”
Section: Resultssupporting
confidence: 86%
“…Presence of the second carbonyl function (assuming it is in α position) results in a higher electrophilicity of the first carbonyl group. Indeed, glyoxal, shown here as the most reactive oxoLPP (15 modification sites), was recently classified as aldehyde with the highest calculated electrophilicity and softness [97], followed by HNE, MDA and HHE [98], which closely resembled the reactivity detected in our study (nine, ten and five modification sites for HNE, methylglyoxal/MDA and HHE respectively). One more reason for the high reactivity of short chain dicarbonyls could be the relatively high hydrophilicity.…”
Section: Resultssupporting
confidence: 86%
“…369373 The cyclopentenone-like eicosanoid electrophile, 15-deoxy-Δ 12,14 -prostaglandin J 2 (15d-PGJ2), was reported to localize in mitochondria and is responsible for inducing ROS formation in endothelial cells. 374 However, previous work has shown that protein targets of 15d-PGJ2 are found in different sites in the cell, including the cytosol and mitochondria, evidencing the pleiotropic nature of the cyclopentenone.…”
Section: Mitochondria-targeted Probes and Sensors For Reactive Oxymentioning
confidence: 99%
“…В свою очередь, протеолитические системы признаются одним из возможных механизмов защиты от накопления окис лительно модифицированных белков и совершенным регулятором протеинового обмена [3,4]. Кроме этого, лизосомаль-ные протеиназы являются важными фак торами развития сердечно-сосудистых за болеваний, в том числе ассоциированных с воспалением [5].…”
Section: ключевые слова: окислительная модификация белков катепсины unclassified
“…Fortheir turn, proteolytic systems are regarded as one of probable protective mech anisms against accumulation of oxidatively modified proteins and as a perfect controller of protein metabolism [3,4]. Besides, lysosomal proteinases are important factors for development of cardiovascular diseases including those associated with inflammation [5].…”
Section: Abstract: Oxidative Modification O F Proteins Cathepsinsb mentioning
confidence: 99%